2010
DOI: 10.1186/1471-2334-10-16
|View full text |Cite
|
Sign up to set email alerts
|

Black race, sex, and extrapulmonary tuberculosis risk: an observational study

Abstract: BackgroundExtrapulmonary tuberculosis is likely a marker of underlying immune compromise. Our objective was to determine race and sex differences in extrapulmonary tuberculosis risk in order to identify the optimal population in which to assess for host factors associated with extrapulmonary tuberculosis.MethodsWe performed an observational study of all tuberculosis cases reported to the Tennessee Department of Health, January 1, 2000 to December 31, 2006. We compared the incidence of extrapulmonary tuberculos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 23 publications
(27 reference statements)
2
46
1
3
Order By: Relevance
“…HIV infection and CVH did not associate with EPTB in our study, although in literature HIV seropositivity and liver cirrhosis are considered risk factors for EPTB [6,8,15]. This difference could be partly due to the lack of analysis on the severity of both diseases.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…HIV infection and CVH did not associate with EPTB in our study, although in literature HIV seropositivity and liver cirrhosis are considered risk factors for EPTB [6,8,15]. This difference could be partly due to the lack of analysis on the severity of both diseases.…”
Section: Discussioncontrasting
confidence: 67%
“…A specific role of geographical origin in the occurrence of EPTB has already been suggested [3,5,6]. For example, Yang et al, found that American Indians and Asians/Pacific Islanders presented an increased risk for EPTB compared with non-Hispanic white subjects [8].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The global test was performed separately within each experimental condition and was controlled for white blood cell (WBC) count. We also controlled for the effect of race (black versus nonblack) because our previous epidemiologic work suggested that blacks were more likely to present with extrapulmonary TB (13). Also, persons of the black race have low numbers of WBCs and differences in monocyte function compared to persons of other races (6,35).…”
mentioning
confidence: 99%
“…While pulmonary tuberculosis can often be reliably diagnosed with imaging and sputum analysis, extra-pulmonary disease may often remain obscure. Tuberculosis lymphadenitis is now the most common extra-pulmonary manifestation of tuberculosis in both HIV positive and negative individuals in the USA (Fiske et al 2010;Heller et al 2010) Isolated abdominal lymphadenopathy especially presents a diagnostic challenge in HIV-infected patients. The dysfunctional immune response in HIV may obscure signs of infection which may lead to atypical clinical presentations (Bos et al 2013;Sinkala et al 2009).…”
Section: Introductionmentioning
confidence: 99%